SOSIALISASI "MATA SEHAT TANPA HP" MELALUI PENGENALAN BUKU CERITA BERGAMBAR UNTUK ANAK USIA DINI - Nuorma Wahyuni; Dila Seltika Canta; Erlin Setyaningsih; Adi Hermawansyah (MAJU : Indonesian Journal of Community Empowerment, 2026)
The Picture book is  an educational media that is able to  enhance the reading interest, imagination, and the ability of  language in the  early childhood. However, the development of digital technology has led the children to use their mobile phone more often than reading the  book. This condition is able to get impact children's eye healthy and the social interaction. This community service activity aims to introduce the picture book is  more educational and enjoyable alternative activity through the socialization of "Healthy Eyes Without Mobile Phones." The implementation method is carried out through socialization, retelling stories, and active interaction with children at one of the Early Childhood Education (PAUD) in Balikpapan City. This activity resulted in children who are enthusiastic about the reading picture book, imagining, and improving children's language literacy and awareness of the importance of maintaining eye health from an early age through  the using of mobile phone.